2018
DOI: 10.5114/pjr.2018.78622
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive evaluation of renal tissue oxygenation with blood oxygen level-dependent magnetic resonance imaging early after transplantation has a limited predictive value for the delayed graft function

Abstract: PurposeThe aim of this study was to evaluate the feasibility of renal oxygenation assessment using blood oxygen level-dependent (BOLD) magnetic resonance imaging (MRI) in the early period after kidney transplantation and to estimate its prognostic value for delayed graft function.Material and methodsExaminations were performed in 50 subjects: 40 patients within a week after the kidney transplantation and 10 healthy controls, using T2*-weighted sequence. Measurements in transplant patients were correlated to ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A strong negative correlation between R2* and RBF was observed in the present study, which may explain the small diagnostic value added by the combination of R2* and RBF compared to RBF values alone. Previous studies (33,34) have evaluated renal function using ASL and BOLD, and reported an 8.3% reduction in the medullary R2* values of transplant patients during a 2-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong negative correlation between R2* and RBF was observed in the present study, which may explain the small diagnostic value added by the combination of R2* and RBF compared to RBF values alone. Previous studies (33,34) have evaluated renal function using ASL and BOLD, and reported an 8.3% reduction in the medullary R2* values of transplant patients during a 2-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies ( 19 , 33 ) have investigated the function of renal allografts using ASL and other functional MRI techniques and have identified renal blood flow and regional renal perfusion as major determinants of oxygen delivery and thus oxygenation of renal tissues. BOLD imaging can detect hypoxic states but may be limited in distinguishing between increased oxygen consumption and decreased blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…BOLD fMRI uses the R2 value, a measure of deoxyhemoglobin in the kidney, and its decrease indicates higher free oxygen availability in the kidney and vice versa. Sławińska et al experimented on patients with early kidney transplantation to detect the blood oxygenation level in the allografts, and they noticed a minimal change in the R2 value, which is a parameter of BOLD fMRI [ 33 ]. Hence it didn't provide any predictive value for the future.…”
Section: Reviewmentioning
confidence: 99%
“…With the use of BOLD imaging, Slawinska et al found higher cortical R2* values in patients with an eGFR ≥ 40 ml/min/1.73 m2 compared to recipients with an eGFR < 40 ml/min/1.73 m2, but R2* was not useful in the prediction of DGF [77]. Thoeny et al compared patients with a stable allograft function with healthy individuals who all underwent DWI and BOLD MRI.…”
Section: Oxygenation Biomarkersmentioning
confidence: 99%